2020
DOI: 10.1186/s13568-020-01081-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a 3D-printable polylactic acid device to optimize a water bioremediation process

Abstract: In the present work, a remediation bioprocess based on the use of a native isolate of Chlorella vulgaris immobilized in an alginate matrix inside a polylactic acid (PLA) device is proposed. This microalga immobilized in alginate beads was previously shown to be useful for the reduction of several chemical and microbial contaminants present in the highly polluted water from the Matanza–Riachuelo watershed. However, these beads had a relatively short shelf life in the natural environment. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…PLA can be used to create frameworks for microbial films in water treatment or soil remediation, gradually degrading into harmless lactic acid ( Farah, Anderson & Langer, 2016 ). Another research work using PLA has led to the creation of a bioremediation system based on using a native isolate of Chlorella vulgaris immobilized onto an alginate matrix inside a PLA device, where the researchers were able to successfully demonstrate the reduction of all inorganic nitrogen forms and total phosphorus by 90% after 5 days, and a 85% decrease in aerobic mesophilic bacteria ( Marconi et al, 2020 ). Polyhydroxyalkanoates (PHAs) are another class of biopolymers produced by bacterial fermentation of sugars or lipids and are completely biodegradable, making them ideal for temporary structures in ecosystem restoration projects ( Kourmentza et al, 2017 ).…”
Section: Materials For 3d Printing In Bioremediationmentioning
confidence: 99%
“…PLA can be used to create frameworks for microbial films in water treatment or soil remediation, gradually degrading into harmless lactic acid ( Farah, Anderson & Langer, 2016 ). Another research work using PLA has led to the creation of a bioremediation system based on using a native isolate of Chlorella vulgaris immobilized onto an alginate matrix inside a PLA device, where the researchers were able to successfully demonstrate the reduction of all inorganic nitrogen forms and total phosphorus by 90% after 5 days, and a 85% decrease in aerobic mesophilic bacteria ( Marconi et al, 2020 ). Polyhydroxyalkanoates (PHAs) are another class of biopolymers produced by bacterial fermentation of sugars or lipids and are completely biodegradable, making them ideal for temporary structures in ecosystem restoration projects ( Kourmentza et al, 2017 ).…”
Section: Materials For 3d Printing In Bioremediationmentioning
confidence: 99%
“…A 3D-printed PLA-carbon black composite with controlled internal porosity was used to remove model VOC contaminants (benzene, toluene, and ethyl benzene) from water [184]. The pseudo-second-order rate constants for the VOC sorption were found to increase with a decrease of internal pore size of this 3D-printed sorbent [185].…”
Section: D Printing Applicationsmentioning
confidence: 99%
“…When Chlorella vulgaris is immobilized in alginate beads, it is useful for the reduction of several chemical and microbial contaminants present in the highly polluted waters. However, alginate beads had a short shelf-life in the natural environment and a 3D-printed PLA composite device was used for the same purpose [184]. The growth kinetics parameters and the bioremediation capacity of immobilized microalgal cells were determined, and it was found that the successful bioremediation of the target water was possible using the novel device, where all inorganic nitrogen forms and total phosphorus were reduced at least by 90% after 5 days of bioprocess in an agitated bioreactor.…”
Section: D Printing Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of materials have been used for PBRs' construction, including glass, LDPE film, clear acrylic (polymethyl methyl acrylate, PMMA, also known by the trade names Plexiglas® and Perspex®), and Polylactic acid (PLA). When it comes to microalgae cultivation, PLA offers several advantages [13][14][15]: Firstly, its non-toxic and biocompatible nature ensures safety in cultivation environments, aligning with environmentally friendly practices owing to its biodegradability. PLA's transparency optimizes light utilization, enhancing the cultivation process, while its commendable thermal stability enables it to withstand moderate temperatures without deformation.…”
Section: Introductionmentioning
confidence: 99%